Pengaruh Lingkungan Kerja terhadap Produktivitas Pegawai pada Puskesmas Lunto Kecamatan Lembah Segar - Nofanza, Rizki; Syamsir, Syamsir (PUBLICNESS: Journal of Public Administration Studies, 2023)
Employee productivity is one of the most important things for every agency because productivity assessments are needed to evaluate employees periodically with the aim of increasing productivity in accordance with agency goals, and to maintain employee morale, this assessment is needed to maintain employee morale. In order for employee productivity to increase, puskesmas need to pay attention to the conditions of the work environment around employees, because with a good work environment, employee productivity can increase and collaboration between employees is encouraged. The work environment is divided into two categories, physical and non-physical. The research here aims to determine the effect of the work environment on employee productivity at the Lunto Health Center, Lembah Segar District. The collection of data used in this study is by using a questionnaire. The population in this study were all employees at the Lunto Health Center, namely 46 employees. The data analysis technique used in this research is multiple linear regression analysis with data analyzer through SPSS v.16 program. The results of this study prove that there is a significant positive effect between the physical and non-physical work environment partially and simultaneously on employee productivity at the Lunto Health Center.